Semiotic Analysis Of The Anime “Attack On Titan” As A Symbol Of Power In The Bstation App - Rendy Renova Dibrata; Mohammad Nuruzzaman (Jurnal Polisci, 2026)
Aims. This study aims to analyze the semiotics in the anime *Attack on Titan* as a sign of power on the Bstation app. Produced by WIT Studio in the first season and MAPPA Studio in the final season, directed by Tetsuro Araki in the first season and Yuichiro Hayashi in the final season, it is adapted from the manga by Hajime Isayama. Methods. This study employs Roland Barthes’ semiotic method within the framework of the Order of Signification, which divides meaning into two stages: denotation—such as military control of evacuations, battles between soldiers and Titans, the king’s presence on the throne, the use of the Founding Titan’s power, Eren’s transformation into a Titan, dialogues rejecting authority, and the Rumbling event that devastated vast regions— Connotation, which carries deeper meanings regarding power relations, domination, and legitimacy. Result. The military is interpreted as a symbol of social control; the death of soldiers reflects individual sacrifice within the system; the puppet king signifies the illusion of formal legitimacy; the manipulation of memory demonstrates control over collective consciousness; Eren’s transformation affirms a shift of power into the individual realm; while the Rumbling represents destructive supremacy. Myths such as heroism, state authority, and individual freedom reveal how power operates, both structurally and personally. Conclusion. The units of analysis in this study consist of key scenes in the anime Attack on Titan that signify practices and power relations, with data sources comprising visual documentation and dialogue from episodes on the Bstation app.